CCND1 silencing suppresses liver cancer stem cell differentiation and overcomes 5-Fluorouracil resistance in hepatocellular carcinoma - Hao Ding (Journal of Pharmacological Sciences, 2020)
Objective: Chemoresistance is one of the major barriers in chemotherapy-based hepatocellular carcinoma (HCC) intervention. 5-Fluorouracil (5-Fu) is a widely used as an anticancer drug. Liver cancer stem cells (LCSCs) are considered the origin of tumor recurrence and resistance. CCND1 (Cyclin D1) plays an important role in tumorigenesis and metastasis in multiple cancers including HCC. Herein, this study was designed to explore the role of CCND1 in regulating LCSCs differentiation and 5-Fu resistance in HCC cells. Methods: The CCND1 mRNA level was examined by qRT-PCR. The protein levels of γ-H2AX (a DNA damage marker) and RAD51 (a DNA repair protein) were examined by Western blot. CD133 was used as a LCSC marker and CD133+ cell percentage in HCC cells was detected by flow cytometry. Results: CCND1 silencing decreased CD133+ cell percentage in HepG2 and SMMC-7721 cells. Furthermore, CCND1 silencing significantly increased protein level of γ-H2AX and decreased that of RAD51 under 5-Fu exposure. Moreover, CCND1 silencing enhanced the sensitivity of HepG2 and SMMC-7721 cells to 5-Fu, which was effectively abrogated by RAD51 upregulation. Conclusion: Collectively, CCND1 silencing suppresses LCSCs differentiation and overcomes 5-Fu resistance in HCC.